2020
DOI: 10.1016/j.cherd.2020.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Production of bio-waste granules and their evaluation as adsorbent for removal of hexavalent chromium and methylene blue dye

Abstract: In this research, compost was used as raw materials in the production of biomass adsorbent granules using drum granulation technique. Different concentrations of aqueous sodium silicate solution were used as the binding agents. Chromium and Methylene Blue solutions were selected as model adsorbates for heavy metals and dyes, respectively. The results obtained showed that the concentration of sodium silicate used had a positive influence on the mechanical strength of the granules, increasing the concentration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…Furthermore, K 1 values decrease with increase in the initial concentration of MB dye, revealing that the adsorption of MB by RC-nZVI is a physical adsorption reaction. The removal of MB by biowaste granules also fitted to pseudo-first-order in a study performed by Jaiyeola et al and another study performed by Sahu et al They found that the adsorption of MB onto nZVI follows the pseudo-first-order kinetic model. The Elovich model effectively describes the interaction between a solid and liquid interface, and takes into account that the real solid surface is energetically heterogeneous and that the desorption process and interactions between adsorbed species have little effect on the adsorption kinetics .…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, K 1 values decrease with increase in the initial concentration of MB dye, revealing that the adsorption of MB by RC-nZVI is a physical adsorption reaction. The removal of MB by biowaste granules also fitted to pseudo-first-order in a study performed by Jaiyeola et al and another study performed by Sahu et al They found that the adsorption of MB onto nZVI follows the pseudo-first-order kinetic model. The Elovich model effectively describes the interaction between a solid and liquid interface, and takes into account that the real solid surface is energetically heterogeneous and that the desorption process and interactions between adsorbed species have little effect on the adsorption kinetics .…”
Section: Resultsmentioning
confidence: 93%
“…Chromium ions and dyes can be released with the industrial effluents of various industries such as steel, electroplating, textile, tannery, leather, paper, food and cosmetics 1 , 2 . The presence of chromium ions and dyes in surface and groundwater has negative impacts on living organisms due to their high toxicity, carcinogenicity, and biorecalcitrance 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The biosorption process is more flexible in both design and operation parts, also the adsorbents, usually with a lower price, can be regenerated and reused after appropriate desorption processes. According to recent studies, various materials, such as treated waste newspaper (Dehghani et al 2016); fruit shell (Anandkumar & Mandal 2009); rice straw (Wu et al 2016); modified seaweed (Yang & Chen 2008); teawaste (Gupta & Balomajumder 2015); sawdust (Meghna & Mondal 2013); bio-waste granules (Jaiyeola et al 2020), banana peel (Chen et al 2022) and so on, have all been examined as biosorbents for Cr(VI) removal from wastewater.…”
Section: Introductionmentioning
confidence: 99%